2001
DOI: 10.1136/gut.49.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Bax expression by mucosal T cells favours resistance to apoptosis in Crohn's disease

Abstract: Conclusions-Regulation of Bcl-2 family protein expression diVers between circulating and mucosal T cells, probably underlying diverse survival potentials. In CD LPT, a low Bax expression and a high Bcl-x L /Bax ratio favour resistance to apoptosis and may contribute to the chronicity of inflammation. (Gut 2001;49:35-41)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
101
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(106 citation statements)
references
References 34 publications
4
101
0
1
Order By: Relevance
“…LPMC from healthy controls showed little expression of the CD44 variant isoforms CD44v4 (median 9%, range 3-11%), CD44v6 (median 8%, range 2-10%) and CD44v7 (median 10%, range 6-15%) ( Table 1). Corroborating our data in experimental colitis, 5 in CD there is a slight upregulation of CD44v6 (median 15%, range 2-24%), while CD44v7 isoforms are significantly upregulated (median 27%, range 16-35%) (Table 1, Figure 1a). CD44v4 is only slightly increased (median 16%, range 10-17%) (Table 1).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…LPMC from healthy controls showed little expression of the CD44 variant isoforms CD44v4 (median 9%, range 3-11%), CD44v6 (median 8%, range 2-10%) and CD44v7 (median 10%, range 6-15%) ( Table 1). Corroborating our data in experimental colitis, 5 in CD there is a slight upregulation of CD44v6 (median 15%, range 2-24%), while CD44v7 isoforms are significantly upregulated (median 27%, range 16-35%) (Table 1, Figure 1a). CD44v4 is only slightly increased (median 16%, range 10-17%) (Table 1).…”
Section: Resultssupporting
confidence: 86%
“…In patients with CD, but not UC, enhanced expression of anti-apoptotic Bcl molecules has previously been described. 5 Therefore, we suggest that signaling through CD44v7 interferes with expression of antiapoptotic molecules of the Bcl family, which explains the proapoptotic effect in LPMC from CD patients, in contrast to UC patients.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…20 Lamina propria T-lymphocytes from patients with Crohn's disease are resistant to apoptosis and express low concentrations of the proapoptotic Bax protein. [21][22][23] It has been shown that binding of infliximab to activated Jurkat T-lymphocytes increases the Bax/Bcl-2 ra-tio, and this results in apoptosis. 24 Moreover, infliximab infusion induces a rapid increase in the number of apoptotic lamina propria T-lymphocytes in patients with active Crohn's disease.…”
mentioning
confidence: 99%
“…Several studies have suggested the resistance of CD T cells to different apoptotic signals [73,74]. It was also demonstrated that IL-6 and the complex formed with its soluble receptor mediates the resistance of T cells to apoptosis in CD contributing to the perpetuation of chronic intestinal inflammation [75].…”
Section: Ulcersmentioning
confidence: 99%